Demographic related quality of life of the aging population in Thailand - Ratmanee, Yodfah; Tongkumchum , Phattrawan (International Journal Of Community Medicine And Public Health, 2023)
Background: Thailand has a substantial elderly population, around one-sixth of its total populace, and ranks second among ASEAN countries. Remarkably, Thailand is the first developing nation to transition into a fully-fledged "Aged Society". This study aimed to assess the quality of life (QoL) of aging in Thailand and explore the demographic factors that affect it. Methods: The QoL and the demographic data of 15,600 adults aged 60 years and over were obtained from Regional Health (RH), Ministry of Public Health, and Thailand. The WHOQOL-BREF instrument in Thai was used to assess aging QoL. Outcome measures included WHOQOL-BREF’s four domains (physical health, psychological, social relationships, and environmental scores. Cronbach’s coefficient assessed the reliability of the questionnaire. The relationships between QoL gender-age group, years, and RHs were investigated using multiple regression. The overall Cronbach’s coefficient of the WHOQOL-BREF questionnaire was 0.94 and Cronbach`s alpha was 0.67, 0.81, 0.72, and 0.87, respectively. Results: The scores of different gender-age groups, years, and RHs significantly differed in the four domains. The younger age for both sexes scored highest in physical, psychological, and environmental domains but not for the youngest females in social relationships. Years show a slight increase in the three domains but not the physical domain. Aging from RH 1-3 had the highest scores for all domains. The WHOQOL-BREF was reliable in the assessment of the QoL of the aging Thai population. Conclusions: To cope with the influencing demographic factors of the QOL, health authorities should support the aging population, especially the oldest physical health.